WHEAT GENETIC RESOURCES IN KYRGYZSTAN - M. Dzhunusova; D. Ten; N. Aubekerova (Вавиловский журнал генетики и селекции, 2014)
Botanical and ecological study of material collected in different areas of Kyrgyzstan showed a broad variability of ecological and morphological forms in wheat landraces. A total of 60 subspecies of spring wheat belonging to 6 species were found. Several ecological groups are recognized in Kyrgyzstan. The most common ecotypes, subrigidum and rigidum, are related to the Iran-Asian subspecies. At the present time, about 80 wheat varieties bred in FSU countries are successfully passing the state variety trial. The following winter and spring wheat varieties were identified on the base of analysis of productivity and quality: Dordoi 16 Mereke 70, Kiyal (st), Suleiman, Kasiet, and Araket. Up to 35 varieties of winter wheat and 12 varieties of spring wheat bred in Kyrgyzstan and abroad are tested annually and recommended for growing in various ecological zones of Kyrgyzstan.